2020
DOI: 10.3168/jds.2019-17677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of butyrate supplementation on blood glucagon-like peptide-2 concentration and gastrointestinal functions of lactating dairy cows fed diets differing in starch content

Abstract: The objective of this study was to evaluate effects of butyrate supplementation on plasma concentration of glucagon-like peptide-2 (GLP-2), apparent total-tract digestibility, and responses to a grain challenge of lactating dairy cows fed diets differing in starch content. Eight Holstein cows averaging 58.6 ± 9.96 d in milk (4 primiparous cows fitted with rumen cannula and 4 multiparous intact cows) were blocked by parity and assigned to one of two 4 × 4 Latin squares balanced for carryover effects with a 2 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…Huhtanen et al (1993) reported that intraruminal infusion of butyrate increased digestibility of neutral detergent fiber (NDF) and organic matter in the total digestive tract. Our previous study also showed that the ingestion of sodium-butyrate increased apparent digestibility of DM and organic matter in the total digestive tract in lactating dairy cows (Fukumori et al, 2020). Guilloteau et al (2009Guilloteau et al ( , 2010 reported that supplementation of sodium-butyrate in milk replacer increased lactase and maltase activities in the small intestines of calves, resulting in improved DM digestibility.…”
Section: Responses To Rumen Acidosis Challengementioning
confidence: 77%
See 1 more Smart Citation
“…Huhtanen et al (1993) reported that intraruminal infusion of butyrate increased digestibility of neutral detergent fiber (NDF) and organic matter in the total digestive tract. Our previous study also showed that the ingestion of sodium-butyrate increased apparent digestibility of DM and organic matter in the total digestive tract in lactating dairy cows (Fukumori et al, 2020). Guilloteau et al (2009Guilloteau et al ( , 2010 reported that supplementation of sodium-butyrate in milk replacer increased lactase and maltase activities in the small intestines of calves, resulting in improved DM digestibility.…”
Section: Responses To Rumen Acidosis Challengementioning
confidence: 77%
“…Butyrate is one of major volatile fatty acids (VFAs) produced by bacterial fermentation. It is known to enhance epithelial growth in the rumen, abomasum, and small intestine in ruminants (Malhi et al, 2013; Mentschel et al, 2001; Sakata & Tamate, 1978) and to enhance nutrient digestibility in lactating cows (Huthanen et al, 1993; Fukumori et al, 2020). Furthermore, in an in vitro study using the livers of lactating cows, sodium butyrate mitigated activation of nuclear factor‐κB and production of inflammatory related cytokines caused by LPS stimulation (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…there is little research evaluating the effects of butyrate supplementation during the calving transition period on performance and inflammation. Much previous research evaluated the effects of butyrate in lactating cows (Herrick et al, 2017;Fukumori et al, 2020;Halfen et al, 2021). Although Kowalski et al (2015) evaluated the effects of butyrate supplementation in cows during the calving transition, butyrate was only supplemented in the close-up period; thus, research assessing the effects of butyrate in the fresh period is lacking.…”
Section: Effects Of Dietary Butyrate Supplementation and Oral Nonster...mentioning
confidence: 99%
“…In contrast, we detected higher serum Hp concentration at d −4 relative to calving in butyrate-fed cows, and no postpartum differences in concentrations of the serum inflammatory markers, SAA and Hp. Fukumori et al (2020) also reported higher serum Hp concentration in cows fed butyrate and suggested that this may be due to gut-specific inflammation as butyrate increases epithelial expression of TLR4, activates the nuclear factor-κB signal pathway, and increases proinflammatory response (Andoh et al, 1999;Hýzd'alová et al, 2008;Xiao et al, 2018). Alternatively, the higher plasma FA concentration on d −4 in butyrate-fed cows may have contributed to increased serum Hp concentration in these cows; elevated serum Hp concentration has been reported alongside increased plasma FA concentrations (Stengärde et al, 2008;Kvidera et al, 2017;Haisain et al, 2021), perhaps due to their associations with fatty liver (Katoh and Nakagawa, 1999).…”
Section: Effect Of Butyrate Supplementationmentioning
confidence: 99%
“…Concentrations of GLP-2 in colostrum were 5.53 ± 1.07 ng/mL (mean ± SE) on average, which was significantly higher ( P < 0.01) than concentrations in plasma of cows at 7 d before the expected parturition date (0.87 ± 0.15 ng/mL on average and ranged from 0.22 to 1.79 ng/mL) and at parturition (d 0) (0.90 ± 0.15 ng/mL on average and ranged from 0.45 to 1.82 ng/mL) in the current study ( Table 2 ). Previous studies have reported that plasma concentrations of GLP-2 were no higher than 1.0 ng/mL in mature sheep [ 22 ] and in lactating dairy cows [ 23 ]. Higher concentrations of hormones in colostrum compared with maternal blood are not unique to GLP-2 because concentrations of insulin and IGF-1 were reported to be higher in colostrum than in maternal blood [ 21 , 24 ].…”
Section: Resultsmentioning
confidence: 99%